Brentuximab vedotin in relapsed/refractory Hodgkin lymphoma: An updated review of published data from the named patient program. (August 2016) - Zinzani, P.L.; Sasse, S.; Radford, J.; Gautam, A.; Bonthapally, V.
Abstract: Brentuximab vedotin was available via named patient program (NPP) to patients with relapsed/refractory (R/R) Hodgkin lymphoma (HL) or systemic anaplastic large-cell lymphoma in ∼60 non-US/Canadian countries, before local approval. Published results were examined recently; through systematic literature review, we identified 12 new NPP publications. Most (10/12) publications included new NPP data describing 8 unique cohorts (N = 480; all R/R HL) and new participating countries. Overall response rates were 58–80%, and complete remission rates were 10–40%. With median follow-up of 9.5–26 months, median progression-free survival was 5–10.5 months and median overall survival (OS) had not been reached in most cohorts; 1- and 2-year OS was 67–76% and 58–67%, respectively. Tolerability was as expected from previous reports. Despite intrinsic bias and heterogeneous cohorts, this update supports previous findings showing comparable efficacy and tolerability of brentuximab vedotin between real-world practice and phase 2 trial results in R/R HL.